Integratif Permainan Tradisional sebagai Strategi Trauma Healing Berbasis Komunitas untuk Anak Korban Bencana: Studi Kontekstual di Sumatera Barat - Satya Gayatri; Reniwati, Reniwati; Bahren, Bahren; Mery Ramadani; Solfiyeni, Solfiyeni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This devotion looks at the effectiveness of traditional Minangkabau games as a medium for healing trauma for children affected by the cold lava disaster of Mount Marapi in West Sumatra. Natural disasters not only have physical impacts, but also psychological ones, especially for children. A culturally based approach is considered relevant to restore children's emotional well-being contextually. This devotion used a descriptive qualitative approach, with data collected through observation, interviews with 36 children, and questionnaires distributed to teachers and parents. The results showed that 88.9% of children preferred traditional games such as tug-of-war, tire racing, and cracker-eating competitions to modern games. These games, which are collaborative and competitive, help reduce stress, rebuild self-confidence, and restore social interaction. Around 83.3% of children were already familiar with these games before the disaster, making familiarity a key factor in fostering a sense of safety and comfort during the recovery process. Trauma symptoms—such as excessive sleepiness, fear, and sleep disturbances—remained, but play activities showed positive impacts. Furthermore, 97.5% of teachers supported the use of traditional games, indicating strong acceptance in the school environment. In addition to serving as an effective psychosocial intervention, traditional games also strengthen cultural identity and community resilience. These findings update and enrich previous research by offering a local context and a child-participatory approach. Thus, traditional games can serve as a strategic alternative for post-disaster trauma recovery in children.